Middle space actors (intermediaries) as translators of global norms: the case of Nepali migrant workers to Malaysia - Khor, Yvonne (Frontiers in Human Dynamics, 2025)
In 2018, a bilateral memorandum of understanding (MoU) was signed by the state authorities of Nepal and Malaysia. Although stringent state regulations have affected the ability of intermediaries to facilitate the movement of migrant workers, this paper highlights the complex practices of various intermediaries along the corridor. A key point in the MoU was the commitment to eliminating migration costs—referred to as “zero cost migration”—and establishing a safe migration pathway that adheres to the International Labour Organisation (ILO) guidelines. However, this study demonstrated that while state policies designed to reflect global norms aimed at reducing exploitative practices in labor migration are well-intentioned, they have inadvertently led to new forms of inequality among migrant workers. This study employed a qualitative methodology, drawing on recent fieldwork conducted from September to December 2024, including semi-structured interviews and participation observations along the Nepal-Malaysia corridor. It analyses data from 40 stakeholder interviews, policy documents and previous migration research projects conducted between 2019 and 2023.